The seismoelectric effect : theory, numerical modeling, laboratory and field experiments /: theory, numerical modeling, laboratory and field experiments. (2017) - Grobbe, Niels; Revil, André, 1970-; Zhu, Zhenya; Slob, Evert C (Evert Cornelis), 1962-
No abstract available